An Integrated Approach for Experimental Design, Control, and Optimization of Perfusion Bioreactors⁎This work was supported by the VINNOVA Competence Centre AdBIOPRO, contract 2016-05181. Issue 2 (2020) - Rodrigues, Diogo
Abstract: This paper presents methods for experimental design, control, and optimization of perfusion bioreactors as well as the vision for their integration. After describing a generic model of perfusion bioreactors, the paper proposes a control scheme via rate estimation and feedback linearization with useful properties with respect to steady-state error, stability, and performance. The paper also introduces data-driven and hybrid procedures for experimental design that are tailored to the intended use of the model for steady-state optimization. Lastly, the methods are illustrated via a simulation example of a perfusion bioreactor.